New Protosmylinae (Neuroptera: Osmylidae) from the early Eocene of western North America, with taxonomic remarks - Makarkin, Vladimir N.; Archibald, S. Bruce; Mathewes, Rolf W. (Zootaxa, 2021)
The osmylid subfamily Protosmylinae is revised based on our emended diagnosis: Petrushevskia Martynova, 1958 and Mesosmylidus Jepson et al., 2012 are excluded (both considered Osmylidae incertae sedis), and Sogjuta Martynova, 1958 is transferred to it from the Mesosmylininae. The late Eocene genus Protosmylus Krüger, 1913 is considered a junior synonym of Osmylidia Cockerell, 1908 based on a distinct apomorphy (deeply forked MA in the hind wing), syn. nov. Three new species of Osmylidia from the early Eocene of North America are described: O. donnae sp. nov. from Quilchena, O. glastrai sp. nov. from Republic, Washington, USA, and an unnamed species of Osmylidia is reported from Driftwood Canyon Provincial Park, British Columbia (all localities of the Okanagan Highlands series), and O. taliae sp. nov. from the Green River Formation of Colorado, USA.